Arkansas - Kirchner, Jason (North Mankato, Minnesota Capstone Press, a capstone imprint, 2017)
"This book uses maps, full color photographs, and easy-to-read text to introduce the state of Arkansas"--
Different countries
Includes bibliographical references and index
1 2 13
Keywords: Arkansas -- Juvenile literature